(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explores the interplay between oral and literary traditions in early Christianity and contemporary African Christian practices. While early Christian communities relied heavily on oral traditions, the transition to written texts significantly shaped the formation of Christian theology and scripture. However, contemporary African Christianity continues to preserve oral traditions, particularly in worship and evangelism. By comparing these two contexts, the study highlights how Reader-Response Theory helps bridge historical and modern interpretive practices. Methodologically, the study employs textual analysis of early Christian writings and fieldwork observations of African Christian communities. Key findings show that oral traditions remain crucial for biblical engagement and theological discourse in low-literacy settings. The study recommends incorporating oral traditions into African Christian theological education to enhance faith practice.